Recommendations for Reopening Endoscopy Units in Turkey: A Set-up Plan from a Tertiary Center in Istanbul - YILMAZ, YUSUF (AVES, 2021)
In the midst of Coronavirus-19 (COVID-19) pandemic, endoscopic procedures have been separated for only urgent and semi-urgent cases for the last few months to prevent transmission in endoscopy units. This approach will perhaps resolve the burden of elective procedures in the months ahead of us. As we observe a downtrend in new cases of COVID-19 in Turkey, a strategy for reopening endoscopy units is required. We are stepping into a time period where we should not only re-provide the essential services to our patients but also maintain the safety of healthcare workers and preserve the valuable personal protective equipment as well. Herein, we aim to share the available knowledge in performing endoscopy during the pandemic and the set-up plan of a tertiary center in Istanbul for reopening the endoscopy unit in the era of the COVID-19 pandemic.
Keywords: Endoscopy; COVID-19; personal protective equipment